2022
DOI: 10.1017/s0954579422001067
|View full text |Cite
|
Sign up to set email alerts
|

Mother and child mental health over time in children with Autism and/or ADHD in the Longitudinal Study of Australian Children

Abstract: This study utilised a longitudinal population-based study to explore mother and child mental health trajectories over time from child age 0 to 14 years, between children with ASD, ADHD, or ASD + ADHD. It explored whether a bidirectional relationship between mother psychological distress and child emotional and behavioural problems (EBPs) existed. The birth cohort from the Longitudinal Study of Australian Children was used. Child EBPs were assessed using the Strengths and Difficulties Questionnaire; and mother … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…One study also found an impact of children's mental health on parental mental health. For example, mothers of children with autism spectrum disorder who also experience emotional and behavioral problems experience increased mental distress (May and Williams, 2022).…”
Section: Results Of the First Tablementioning
confidence: 99%
“…One study also found an impact of children's mental health on parental mental health. For example, mothers of children with autism spectrum disorder who also experience emotional and behavioral problems experience increased mental distress (May and Williams, 2022).…”
Section: Results Of the First Tablementioning
confidence: 99%
“…Rearing children and adolescents with neurodevelopmental disorders (NDD) is often associated with elevated parental stress [1][2][3] and increased risk of mental health problems, such as anxiety and depression [4][5][6][7][8], especially in parents of children with autism spectrum disorder (ASD) [9][10][11]. Evidence suggests that parental stress is driven by child behavioral difficulties [3,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%